Top 3 differentials in neuroradiology a case review - O'Brien, William T. (Thieme, 2015)
Top 3 Differentials in Neuroradiology is an up-to-date, comprehensive review of critical topics in neuroimaging. The books unique format ranks the differentials, divides them into the Top 3, and presents additional diagnostic considerations for each case presentation. The discussion sections of each case cover the imaging and clinical manifestations for all disease processes, making this text a high-yield review for board exam preparation and a quick reference for daily clinical practice